209k views
0 votes
Solve the following for x.
3(x-4)-x+7=(4x+9)+(x-32)

1 Answer

5 votes

Answer:

x= 6

Explanation:

3(x-4)-x+7= (4x+9)+(x-32)

Distribute 3 through the parenthesis.

3x-12-x+7=4x+9+(x-32)

When there is a "+" in front of the parenthesis the expression remains the same.

3x-12-x+7= 4x+9+x-32

Collect the like terms.

2x-12+7= 4x+9+x-32

Calculate the sum.

2x-5=4x+9+x-32

Collect the like terms.

2x-5= 5x+9-32

Calculate the difference.

2x-5= 5x-23

Move the variable to the left side and change the sign.

2x-5x+5= -23

Move the constant to the right side and change its sign.

2x-5x= -23+5

Collect the like terms.

-3x=-18

Divide both sides of the equation by -3.

-3x= -18

-3 -3

Solution:

x= 6

User Ravi Yenugu
by
5.4k points